Dynamics of binary mixtures of an ionic liquid and ethanol by NMR. (10th July 2017) - Ordikhani Seyedlar, Amin; Martins, João Pedro de Almeida; Sebastião, Pedro J.; Jardim Beira, Maria José; Stapf, Siegfried; Vaca Chávez, Fabián; Mattea, Carlos
Abstract : A study of molecular dynamics of the ionic liquid 1‐ethyl‐3‐methylimidazolium bis(trifluoro‐methylsulphonyl)imide ([Emim][Tf2N]) in solution with deuterated ethanol at different molar concentration and temperatures is presented. The study was performed using 1 H and 2 H nuclear magnetic relaxation and 2 H 1D spectroscopy. The temperature dependence of the spin–lattice relaxation time T 1 of the cations allows the evaluation of the activation energies of the rotational degree of freedom of these molecules. The viscosity in the binary system increases with the concentration of ionic liquid. However, the activation energy in the cation molecules decreases when the concentration of the ionic liquid increases, indicating that the rotational dynamics is facilitated. This behavior is explained from the fact that the presence of the ionic liquid in the system disrupts the degree of intermediate range order expected in the alcohol system. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The molecular dynamics of binary mixtures of the ionic liquid [Emim][Tf2N] in solution with deuterated ethanol at different molar concentration is presented. The study was performed using 1 H and 2 H nuclear magnetic relaxation and 2 H 1D spectroscopy. The results are explained from the fact that the presence of the IL in the system disrupts the degree of intermediate range order expected in the alcohol system.